UJI EFEKTIVITAS BEBERAPA KONSENTRASI EKSTRAK DAUN KETAPANG (Terminalia catappa L.) TERHADAP ULAT GRAYAK (Spodoptera litura) SECARA IN VITRO - Riski Nella Sari Batubara; Yusmar Mahmud; Rita Elfianis (DINAMIKA PERTANIAN, 2021)
Spodoptera litura is one of the important plant pests that are polyphagic. Spodoptera litura attacks can cause damage to up 80% on plants causing losses for framer. Control using synthetic pesticides is excessive because it causes negative for environment. Efforts that can be made are using biopesticides such as Terminalia catappa L. leaves. This research aims to obtain effective concentrations in controlling Spodoptera litura in vitro. The research was carried out in Pathology, Entomology and Microbiology, Faculty of Agriculture and Animal Husbandry and experimental farm of State Islamic University of Sultan Syarif Kasim from February to March 2019. This research used a Completely Randomized Design with 5 treatments, consisting of control, 9% EDK, 18% EDK, 27% EDk and 36% EDK with 3 replications. The parameters used are larvae stop eating (%), speed of death, mortality, toxicity of LC50 and larvae become pupae (%). The result showed the effective concentration in controlling Spodoptera litura was EDK 18%.